Children’s Character Learning Model Based on Indonesian Local Wisdom: Implemented to Early Childhood Education in Play Centers - Nurani, Yuliani; Niken Pratiwi; Situmorang, Robinson; Ni Gusti Ayu Made Yeni Lestari (JURNAL PENDIDIKAN USIA DINI, 2024)
Character education can equip young children to become Indonesia's golden generation who are superior and skilled in noble work. This research aims to produce an early childhood character learning model based on local Indonesian wisdom through the Playing Center title which will be implemented at Early Childhood Education Institutions (ECE) in Indonesia. This research method uses the steps of the Borg and Gall research and development model. The subjects in this research were 30 teachers from five ECE institutions in the DKI Jakarta area. The data used as the basis for building a framework for early childhood character learning models based on local intelligence were collected using observation and interview techniques. The findings show that the teacher prepares a learning plan program at the beginning of each semester which is listed in the weekly program and daily program. However, the teacher has not fully prepared a simulation program that leads directly to the introduction of early childhood character. Identification of character values ​​in early childhood is done by providing examples of behavior and speech at school. The media that has been used to identify children's characters is through posters and non-digital story books. The learning environment needs to be improved because teachers have not been optimal in organizing the play environment in providing stimulation to children in class. The results of this research will enrich the character education model following the potential of the institution and the cultural background of early childhood as Indonesia's golden generation. Keywords: character learning model, local wisdom, play center, early childhood References: 1 Abu Nawas, M. Z., Sulaiman, U., Darnanengsih, D., & Rusyaid, R. (2022). Harmony in The Frame of Local Wisdom “One Furnace-Three Stones” in Education. Dinamika Ilmu, 22(1), 109–130. https://doi.org/10.21093/di.v22i1.4284 Anderson-McNamee, J. K., & Bailey, S. J. (2010). The Importance of Play in Early Childhood Development. MontGuides, 1–4. Anderson, R., & Thomas, H. (2021). Engaging With Play-Based Learning. The Journal Of Teacher Action Research, 7(2), 56–69. Aningsih, Zulela, M. S., Neolaka, A., Iasha, V., & Setiawan, B. (2022). How is the Education Character Implemented? The Case Study in Indonesian Elementary School. Journal of Educational and Social Research, 12(1), 371–380. https://doi.org/10.36941/jesr-2022-0029 Betawi, A. (2020). Calling for character education: promoting moral integrity in early childhood education in Jordan. Early Child Development and Care, 190(5), 738–749. https://doi.org/10.1080/03004430.2018.1489383 Borg, W. R., & Gall, M. D. (1983). Educational Research: An Introduction (4th Editio). Longman Inc. Bredemeier, B. L., & Shields, D. L. (2019). Social Justice, Character Education, and Sport: A Position Statement. Quest, 71(2), 202–214. https://doi.org/10.1080/00336297.2019.1608270 Demir, M., & Kaya, M. (2022). Analysis of Constructivist Learning Model’s Effects on Student Outcomes: A Second Order Meta-Analysis Yapılandırmacı Öğrenme Modelinin Öğrenci Çıktılarına Etkisinin İncelenmesi: Second Order Meta -Analiz. Journal of Theoretical Educational Science, 15(October), 938–957. kaya Edwards, S., & Cutter-Mackenzie, A. (2013). Pedagogical Play Types: What Do They Suggest for Learning About Sustainability in Early Childhood Education? International Journal of Early Childhood, 45(3), 327–346. https://doi.org/10.1007/s13158-013-0082-5 Fleer, M. (2011). “Conceptual play”: Foregrounding Imagination and Cognition During Concept Formation In Early Years Education. Contemporary Issues in Early Childhood, 12(3), 224–240. https://doi.org/10.2304/ciec.2011.12.3.224 Harun, Jaedun, A., Sudaryanti, & Manaf, A. (2020). Dimensions of early childhood character education based on multicultural and community local wisdom. International Journal of Instruction, 13(2), 365–380. https://doi.org/10.29333/iji.2020.13225a Hasani, A. (2016). Educational Research and Reviews Enhancing Argumentative Writing Skill Through Contextual Teaching and Learning. Academic Journals, 11(16), 1573–1578. https://doi.org/10.5897/ERR2016.2806 Hoorn, J. Van, Nourot, P. M., Scales, B., & Alward, K. R. (2014). Play at the Center of the Curriculum (J. W. Johnston, J. Peters, & A. Hall (eds.); Sixth). Pearson. Ima, W., Pattiasina, J., & Sopacua, J. (2023). Model to increase motivation and learning outcomes in learning history. Journal of Education and Learning, 17(2), 206–214. https://doi.org/10.11591/edulearn.v17i2.20703 Jumiaan, I., Alelaimat, A., & Ihmeideh, F. (2020). Kindergarten teachers’ knowledge level of developmentally appropriate practice in Jordan. Education 3-13, 48(8), 1000–1011. https://doi.org/10.1080/03004279.2019.1699939 Kokoszka, C., & Smith, J. (2016). Fostering Character Education in an Urban Early Childhood Setting. Journal of Character Education, 12(1), 69–74. https://eric.ed.gov/?q=character+education+in+early+childhood+&id=EJ1151327 Krisna, D., Gunarhadi, G., & Winarno, W. (2020). Development of Educational Comic with Local Wisdom to Foster Morality of Elementary School Students: A Need Analysis. International Journal of Educational Methodology, 6(2), 337–343. https://doi.org/10.12973/ijem.6.2.337 Lee, G.-L. (2013). Re-emphasizing Character Education in Early Childhood Programs: Korean Children’s Experiences. In Childhood Education (pp. 315–322). https://doi.org/: http://dx.doi.org/10.1080/00094056.2013.830907 Mackenzie, A. C., Edwards, S., Moore, D., & Boyd, W. (2014). Young Children’s Play and Environmental Education in Early Childhood Education. Springer. Multazam, M., Syahrial, Z., & Rusmono. (2023). Development of Learning Models in Web Programming Courses With Computer-Based Learning Tutorials. Turkish Online Journal of Distance Education, 24(2), 232–244. https://doi.org/10.17718/tojde.1081507 Mulyadi, B. (2019). Model Pendidikan Karakter Anak Usia Dini Dan Anak Usia Sekolah Dasar Di Jepang. Kiryoku, 3(3), 141. https://doi.org/10.14710/kiryoku.v3i3.141-149 NAEYC. (2012). Technology and Interactive Media as Tools in Early Childhood Programs Serving Children from Birth through Age 8. Children, January, 1–15. http://www.naeyc.org/positionstatements Nuraeni, L., Andrisyah, A., & Nurunnisa, R. (2019). Efektivitas Program Sekolah Ramah Anak dalam Meningkatkan Karakter Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(1), 20. https://doi.org/10.31004/obsesi.v4i1.204 Nurani, Y., & Pratiwi, N. (2018). Pembelajaran Tematik Integratif Berbasis Karakter Dalam Menstimulasi Keterampilan Vokasional Anak Usia 5-6 Tahun. Seminar Nasional Dan Call for Paper “Membangun Sinergitas Keluarga Dan Sekolah Menuju PAUD Berkualitas, 168–171. Nurani, Y., & Pratiwi, N. (2020a). Curriculum Design of Early Childhood Life Skill Based on Indonesian Local Culture. 422(Icope 2019), 333–337. https://doi.org/10.2991/assehr.k.200323.145 Nurani, Y., Pratiwi, N., & Hasanah, L. (2022). Digital Media based on Pancasila Values to Stimulate Character Building in Early Childhood. Journal for ReAttach Therapy and Developmental Diversities, 5(1), 41–49. Olao, E. M., Misigo, B. L., & Speck, K. (2021). Using Participatory Visual Methods To Teach Character Education in Early Childhood in Kenya. European Journal of Education Studies, 8(6), 208–223. https://doi.org/10.46827/ejes.v8i6.3793 Pamungkas, J., Suyuti, S. A., & Rohman, A. (2021). Character Value that Formed Through Learning the Art of Playing GACIL in Early Childhood. Cypriot Journal of Educational Sciences, 16(4), 1503–1516. https://doi.org/10.18844/cjes.v16i4.6004 Plowman, L., Stephen, C., & McPake, J. (2010). Supporting young children’s learning with technology at home and in preschool. Research Papers in Education, 25(1), 93–113. https://doi.org/10.1080/02671520802584061 Rokhman, F., Hum, M., Syaifudin, A., & Yuliati. (2014). Character Education for Golden Generation 2045 (National Character Building for Indonesian Golden Years). Procedia - Social and Behavioral Sciences, 141, 1161–1165. https://doi.org/10.1016/j.sbspro.2014.05.197 Saptatiningsih, R. I., & Permana, S. A. (2019). Early Childhood Character Building Troughtechnological Education. Journal of Physics: Conference Series, 1254(1). https://doi.org/10.1088/1742-6596/1254/1/012048 Sheridan, M. D. (2011). Play In Early Childhood: From Birth To Six Years (3rd editio). Routledge. Smolucha, L., & Smolucha, F. (2021). Vygotsky’s theory in-play: early childhood education. Early Child Development and Care, 191(7–8), 1041–1055. https://doi.org/10.1080/03004430.2020.1843451 Sop, A., & Biskin, S. Ö. (2021). Character Strengths in Early Years: Teachers’ Awareness and Practices. Journal of Teacher Education and Educators, 10(2), 227–253 Srianita, Y., Akbar, M., & Meilanie, S. M. (2019). Pembentukan Karakter dalam Pendidikan Makan (Studi Kasus di Raudhatul Athfal Istiqlal Jakarta). Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(1), 152. https://doi.org/10.31004/obsesi.v4i1.277 the Integration of Sentra-Based Learning and Involvement of Family Program At Early Childhood in Developing Character Building (Multi Case At Paud Mawaddah and Paud Alam Berbasis Karakter Sayang Ibu Banjarmasin, Indonesia). (2018). European Journal of Education Studies, 5, 49–63. https://doi.org/10.5281/zenodo.1494207 Turan, F., & Ulutas, I. (2016). Using Storybooks as a Character Education Tools. Journal of Education and Practice, 7(15), 169–176. www.iiste.org Tussubha, N., & Hadiyanto. (2020). Integrated Character Education Model in Early Childhood Education Based on Minangkabau Local Culture: Randai. 449(Icece 2019), 5–12. https://doi.org/10.2991/assehr.k.200715.002 Warsiti. (2015). Pembelajaran Berbasis Budaya Lokal dalam Membentuk Karakter Toleransi pada Anak Kelompok B di TK Negeri Pembina Kabupaten Purbalingga. Skripsi, 1–90. Xu, Y. (2010). Children’s Social Play Sequence: Parten’s Classic Theory Revisited. Early Child Development and Care, 180(4), 489–498. https://doi.org/10.1080/03004430802090430 Yadav, S., & Vyas, P. C. (2021). Impact of Digital Technology on Preschoolers : A Review. International Journal of Scientific Research in Science and Technology, 223–227. https://doi.org/10.32628/ijsrst218232